MAINTENANCE IMPLEMENTATION THROUGH MARINE ERP SYSTEMS - Adamantidis, Vasileios (Revista Ciências Exatas, 2023)
This research paper aims to examine how marine Enterprise Resource Planning (ERP) systems implement maintenance plans in the maritime industry. The objectives of this paper were to examine the evolution of maintenance practices in the maritime industry and the emergence of marine ERP systems as a transformative solution. It also investigates the role of marine ERP systems in optimizing maintenance planning and execution. The article further assessed the financial implications of implementing marine ERP systems for maintenance and explores the alignment between marine ERP systems and environmentally sustainable maintenance practices. The method used in this study was the quantitative technique and the data was collected using the questionnaire survey. The data collected has been analysed using SPSS software to evaluate how maritime ERP systems relate to different facets of maintenance effectiveness. The research's primary target areas are operational effectiveness, cost-cutting, safety improvement, and environmental sustainability. The results revealed that incorporating marine ERP systems in maintenance practices positively impacts all aspects analysed. The study advances knowledge of how technology-driven efforts, such as ERP systems, can transform the maintenance environment in the maritime industry for enhanced operational performance and overall excellence.